Organic farm produce in Kerala - an economic analysis - Dana K (Department of Agricultural Economics, College of Horticulture, 2007)
The present study on the “Organic farm produce in Kerala – An economic analysis" was conducted to analyse supply pattern, marketing practices, constraints in production and marketing and to study the consumer awareness regarding organic produce. The study was based on the data collected from Poothadi and Panamaram panchayaths in Wayanad districts, where organic farming is taken up on a commercial scale.